Mindfulness-based intervention to reduce burnout and psychological distress, and improve wellbeing in psychiatry trainees: a pilot study. (June 2019) - Kang, Matthew; Selzer, Rob; Gibbs, Harry; Bourke, Katie; Hudaib, Abdul-Rahman; Gibbs, Jo
Background: Healthcare professionals including psychiatry trainees experience high amounts of occupational stress. This pilot study aims to assess the impacts and feasibility of a mindfulness-based intervention program as an occupational intervention in a metropolitan hospital. Method: Psychiatry trainees participated in an mindfulness-based intervention training program consisting of 1-h weekly sessions over 8 weeks. Levels of psychological distress and mindfulness were measured pre and post-intervention. Qualitative data through an open-ended feedback survey were also collected. Results: There was an improved level of mindfulness and a decreased level of burnout among trainees post-intervention. Advantages of the program included having a compassionate facilitator and the program being tailored to healthcare staff. Limiting factors included time restraints and clinical responsibilities. Conclusion: Psychiatry trainees can benefit from an occupational MBI program. This can positively impact their health as well as improve their work performance. A number of factors important for implementation of a mindfulness-based intervention program were also identified.